Exposure to Empowerment in COVID-19: Healthcare workers' resilience for future Pandemics - Rashmi Ranjan Guru; Subhodip Mitra; Meenakshi Vyas; Vipin Koushal; Navin Pandey; Sumit Kumar; Ashok Kumar; Manisha Biswal; Soujanya Kumar (National Board of Examinations Journal of Medical Sciences, 2025)
Background: The COVID Health Care Workers (HCWs) were committed to the treatment of COVID patients during the pandemic. In this process, there was a high chance of acquiring and/or carrying the deadly infection to themselves as well as to their family members. Hence it was imperative to take all the necessary steps to provide protection to the HCWs, confining the spread of the virus. Using the WHO (World Health Organization) risk assessment tool, many researchers had evaluated the probability of spreading of COVID infection. In this paper, we tried to assess the risk of HCWs exposed to COVID-19 patients during the pandemic. Methods: A prospective cross-sectional study was carried out from August 2020 to August 2021 using WHO (World Health Organization) risk assessment tool. A total of 1600 HCWs, who worked in the COVID hospital were included in the study. The HCWs were divided into two groups high-risk group and a low-risk group. The HCWs who got confirmed exposure to COVID patients or their infected material were included in the high-risk group and others were included in low-risk group. The chi-square test and binary logistic regression analysis were done by using the SPSS 24 statistics application. Results: Females were more prone to the risk of infection than their male counterparts [OR 1.9 (1.13-3.28), p=0.015]. HCWs with confirmed exposure to COVID-19 patients were more prone to the risk of infection [OR 196.9 (19.78-1960.7), p=0.001]. The HCWs who were exposed to the biological secretory materials of the COVID-patients were more prone to COVID-19 infection, including the needle stick injury [OR 0.229 (0.056-0.931), p=0.039]. Conclusions: The study revealed that HCWs in the high-risk group were less infected than the low-risk group, which contradicts the common perception of HCWs that they will get an infection after the COVID duty.